Gramsci, Class and Post-Marxism - Donaldson, Mike (International Gramsci Journal, 2023)
Often Gramsci is presented in the social sciences, particularly by post-Marxists, as a precursor of and justification for abandoning the concept of class. This is incorrect. This article outlines Gramsci’s ideas of class, class composition, formation and alliance which Gramsci based on a detailed, accurate reconnaissance of the Italy of his time.